Counterterrorism and cybersecurity : total information awareness - Lee, Newton (Springer New York, 2013)
Imagine James Bond meets Sherlock Holmes: Counterterrorism and Cybersecurity is the sequel to Facebook Nation in the Total Information Awareness book series by Newton Lee. The book examines U.S. counterterrorism history, technologies, and strategies from a unique and thought-provoking approach that encompasses personal experiences, investigative journalism, historical and current events, ideas from great thought leaders, and even the make-believe of Hollywood. Demystifying Total Information Awareness, the author expounds on the U.S. intelligence community, artificial intelligence in data mining, social media and privacy, cyber attacks and prevention, causes and cures for terrorism, and longstanding issues of war and peace. The book offers practical advice for businesses, governments, and individuals to better secure the world and protect cyberspace. It quotes U.S. Navy Admiral and NATO's Supreme Allied Commander James Stavridis: "Instead of building walls to create security, we need to build bridges." The book also provides a glimpse into the future of Plan X and Generation Z, along with an ominous prediction from security advisor Marc Goodman at TEDGlobal 2012: "If you control the code, you control the world." Counterterrorism and Cybersecurity: Total Information Awareness will keep you up at night but at the same time give you some peace of mind knowing that "our problems are manmade - therefore they can be solved by man [or woman]," as President John F. Kennedy said at the American University commencement in June 1963.